Internal control systems in promoting sound governance; a case study of Manyame rural district council - Nyawo, Lloyd (Midlands State University, 2018)
Delivering effective governance have been identified as a steering wheel for development and developing countries have been encouraged to be effective and efficient in the provision of services .However many developing countries especially in Africa are characterised by poor governance and unethical practices which then impedes development and local economic growth. There have been efforts by international organisations such as the United Nations and SADC to try and reduce the injustices and internal controls among other strategies were regarded as a panacea to sound governance. Thus this study will try to unfold how internal control systems improve sound governance. Furthermore the study aimed at identifying the forms of internal controls systems at Manyame RDC, demonstrating how internal control systems have been used to promote sound governance, examining the core relationship between internal controls and governance, assessing the effectiveness of internal control systems in promoting good governance, examining the measures that have been put in place to strengthen the control systems and also recommending methods that can be used strengthen internal controls and good governance. An integrated internal control model was used in trying to highlight the major components of internal controls. More so, compliance and integrity approaches are used in the implementation of effective controls. There is a strong relationship between internal controls and governance in that the former have negative implications on the latter if the systems and procedures of the organisation are very weak. Thus it is imperative for organisations to solidify their control systems so as to establish a more comprehensive corporate governance framework. Strong internal control systems provide a guiding menu for a more effective, efficient, accountable, and transparent and honesty way of doing business. A comparative analysis of the governance practises in Singapore, Tanzania and Zimbabwe was employed so as to identify effective ways of promoting governance and increasing organisational performance in public sector. The research employed both qualitative and quantitative methods in the collection of data through interviews, questionnaires and observations. The research targeted 32 respondents which comprised of management ,technicians ,clerks and general employees in the departments of Finance ,Administration, Audit ,Planning and Engineering .Furthermore the research identified that lack of independence, resources, lack of understanding on the importance of internal controls, failure to implement auditor’s recommendations impedes effective implementation of a sound control system in local authorities .The research identified that it is critical to establish a separate reporting structure of internal audit so as to allow its independence. In addition it has been recommended that there is need to foster mutuality between management and internal audit so as for the systems to be effective.